2007
DOI: 10.1071/sh06063
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and condom use with clients among female sex workers in China

Abstract: This study examines the association between depressive symptoms and condom use with clients among 278 female sex workers (FSW) in Guangxi, China. About 62% of these FSW had a high level of depressive symptoms (CES-D total score ≥ 16). Multiple logistic regression analyses indicated that FSW with high level of depressive symptoms were less likely to use condoms consistently (aOR = 0.50, 95% CI: 0.28-0.89) or use condoms properly (aOR = 0.44, 95% CI: 0.20-0.99). The findings suggested that HIV prevention program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 22 publications
9
71
1
2
Order By: Relevance
“…Consistent with previous studies, a significant proportion of FSWs and drug users reported mental health problems, such as hopelessness or depressive symptoms; and IDUFSWs were more likely than the general female IDUs to report hopelessness and depressive symptoms (Silbert, Pines, & Lynch, 1982;Miller, Mahler, & Gold, 1991;Paone et al, 1999;Burns et al, 2004;Hong et al, 2007).…”
Section: Mental Health Problems and Hiv-related Risk Behaviors Among supporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with previous studies, a significant proportion of FSWs and drug users reported mental health problems, such as hopelessness or depressive symptoms; and IDUFSWs were more likely than the general female IDUs to report hopelessness and depressive symptoms (Silbert, Pines, & Lynch, 1982;Miller, Mahler, & Gold, 1991;Paone et al, 1999;Burns et al, 2004;Hong et al, 2007).…”
Section: Mental Health Problems and Hiv-related Risk Behaviors Among supporting
confidence: 77%
“…Studies suggest that women with such negative affects are ill-equipped to deal with the additional stress of insisting on condom use during sex work (O'Leary, 1995). Depression has been associated with inconsistent condom use with sex work clients (Hong et al, 2007;Stevenson & Petrak, 2007), while hopelessness and pessimism have been associated with high risk sexual behaviors among FSWs (Silbert, Pines, & Lynch, 1982;Paone et al, 1999). FSWs with poor interpersonal or social support are also less likely than others to be consistent condom users during sex work (Dandona et al, 2005;Campbell, 2000).…”
Section: Mental Health and Interpersonal Problems Among Idus Fsws Amentioning
confidence: 96%
“…The underreporting in the current study might be largely due to low 28 Another major deterrent to STI testing was the strong stigma associated with commercial sex, as previous studies suggested that self-perceived stigma has led to increased sexual risks, including delayed testing or treatment. 29 Therefore, interventions aimed at reducing the STI epidemic in FSWs should not only focus on reducing sexual risks among FSWs and their clients but also increase their awareness and motivation to access STI=HIV testing. Structural interventions at a society level are needed to reduce the stigma against FSWs and create a positive environment for them to seek preventive care and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The validated Chinese version showed good internal reliability (Cheung and Bagley, 1998;Chi and Boey, 1993;Song et al, 2008) and has been used in studies targeting key populations such as female sex workers (Hong et al, 2007) in China. Participants rated how often they have experienced depressive symptomatology in the past 7 days, on a four-point Likert scale ['rarely or none of the time (less than 1 day)' to 'almost or all of the time (5-7 days)'].…”
Section: Probable Depressionmentioning
confidence: 99%